Risk factor analysis and nomogram construction of postoperative complications for patients with locally advanced gastric cancer who received neoadjuvant immunotherapy and chemotherapy - Cui, Hao; Zhang, Sijin; Sun, Linde; Yuan, Zhen; Xu, Qixuan; Gao, Jingwang; Chen, Lin; Cui, Jianxin; Wei, Bo (Frontiers in Medicine, 2024)
Introduction The combination of neoadjuvant chemotherapy and immunotherapy (NICT) has become the common scheme for locally advanced gastric cancer (LAGC). However, the safety and efficacy of radical gastrectomy following NICT (NICT-G) remain controversial. This study aimed to analyze the risk factors affecting postoperative complications (POCs) after NICT-G and construct a nomogram to provide a clinical reference for predicting POCs. Methods This study enrolled 177 patients receiving NICT-G in the Chinese PLA General Hospital First Medical Center from January 2020 to January 2024. Uni-and multivariable logistic regression models were used to evaluate the risk factors influencing POCs, and a nomogram model was constructed. To evaluate the discrimination and accuracy of the nomogram model, the area under the receiver operating characteristic curve (AUC) and the calibration curve were used. ResultsThe pathological complete response and major pathological response rates were 15.8% and 45.2%, respectively, whereas the overall and severe treatment-related adverse events rates were 71.8% and 15.8%, respectively, in 177 patients receiving NICT-G. Forty-three (24.3%) patients developed overall POCs (Clavien-Dindo classification ≥ II). Uni-and multivariable logistic analyses showed that age ≥ 70 years, more estimated blood loss, platelet/lymphocyte ratio (PLR) ≤ 196, neutrophil/lymphocyte ratio (NLR) > 1.33, non R0 resection, and body mass index (BMI) < 18.5 kg/m 2 were independent risk factors for overall POCs (P < 0.05). The nomogram model developed using the abovementioned variables showed that the AUC (95% confidence interval [CI]) was 0.810 (95% CI: 0.733-0.888) in predicting POC risk. The calibration curves showed that the prediction curve of the nomogram was good in fit with the actual POCs (Hosmer-Lemeshow test: χ 2 = 4.59, P = 0.800). Conclusion Age ≥ 70 years, more estimated blood loss, PLR ≤ 196, NLR > 1.33, non R0 resection, and BMI < 18.5 kg/m 2 were independent risk factors for overall POCs in the NICT-G. A nomogram constructed on the basis of the abovementioned indicators showed better accuracy for predicting POC risk.